Wicked beauty eaudiobook - Robert, Katee (Dark Olympus, 2022)
In Olympus, you either have the power to rule...or you are ruled. Achilles Kallis may have been born with nothing, but as a child he vowed he would claw his way into the poisonous city's inner circle. Now that a coveted role has opened to anyone with the strength to claim it, he and his partner, Patroclus Fotos, plan to compete and double their odds of winning. Neither expect infamous beauty Helen Kasios to be part of the prize...or for the complicated fire that burns the moment she looks their way. Zeus may have decided Helen is his to give away, but she has her own plans. She enters into the competition as a middle finger to the meddling Thirteen rulers, effectively vying for her own hand in marriage. Unfortunately, there are those who would rather see her dead than lead the city. The only people she can trust are the ones she can't keep her hands off of—Achilles and Patroclus. But can she really believe they have her best interests at heart when every stolen kiss is a battlefield?